Gas exchange and bioactivity in yellow passion fruit seedlings cv. Rubi do Cerrado under organic substrates and water levels - L. A. P. Silva-Filho; E. F. Mesquita; C. S. Sousa; J. P. C. Diniz; S. N. Silva (Brazilian Journal of Biology)
Abstract Fertilization and water supply are indispensable factors in the initial growth of passion fruit and, consequently, in its production in the field. The aim of this study was to evaluate the influence of organic substrates and water levels on gas exchange and bioactive compounds in passion fruit seedlings (cv. BRS Rubi do Cerrado). The treatments consisted of a 5 × 2 factorial arrangement, comprising five organic substrates: S1= 100% soil, S2= 75% soil and 25% cattle manure, S3= 75% soil and 25% goat manure, S4= 75% soil and 25% worm humus, S5= 75% soil and 25% organic compost and two water levels: L1 50% and L2 100% of water available in the substrate, with six replicates. Gas exchange was analyzed: stomatal conductance - gs, transpiration - E, CO2 assimilation rate - A and internal CO2 concentration - Ci. From the data obtained, the instantaneous water use efficiency - EiUA and the instantaneous carboxylation efficiency - EiCi were estimated, as well as the bioactive compounds: total carotenoids, chlorophyll a and b, phenolic compounds and proline. When the seedlings were irrigated with 100% available water, they showed higher stomatal conductance, transpiration, CO2 assimilation rate and internal CO2 concentration, resulting in greater carboxylation. Seedlings grown in substrates containing cattle manure and worm humus showed better responses to water deficit. There was an influence of the different substrates and water levels on the gas exchange and bioactive compounds of passion fruit seedlings cv. Rubi do Cerrado.